Reactualization of Islamic Education Based on Culture to Build National Character in the Era of Globalization (Study of Baritan Tradition in Ngeni Village, Blitar District) - Wulandari, Selvi; Ayundasari, Lutfiah (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
This research was conducted based on the crucial issue of education. Globalization provides benefits for countries to develop, but is not conducive to character education. Globalization brings many new values that cause the implementation of moral, cultural and religious values in children to decline. Education is the key to forming a young generation with character, so reactualization needs to be pursued. Character education is closely related to Islamic education. Many local traditions hold cultural and religious values, including the baritan tradition preserved by the community in Ngeni Village, Blitar Regency. The purpose of this research is the reactualization of Islamic education, especially culture-based by taking Islamic values in the baritan tradition.  This research uses descriptive qualitative research to present research based on natural settings. The results showed that in the midst of globalization, character education requires refreshment, so that local culture is not displaced by foreign cultures. In the baritan tradition, there are cultural and religious values that must be introduced and taught to the younger generation so that they do not fade and disappear in the times. The reactualization process is carried out through four steps, namely exemplary, habituation, supervision, and punishment and reward.